2017
DOI: 10.1186/s40364-017-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of the role of serum albumin in cardiovascular disease

Abstract: Concentration of serum albumin (SA), a multifunctional circulatory protein, is influenced by several factors, including its synthesis rate, catabolism rate, extravascular distribution, and exogenous loss. Moreover, both nutritional status and systemic inflammation affect the synthesis of SA. Determining SA concentration aids in risk prediction in various clinical settings. It is of interest to understand the prognostic value of SA in the full spectrum of cardiovascular disease (CVD) in the era of newly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 70 publications
5
97
1
1
Order By: Relevance
“…smoking), absorption disorder, hypercatabolic state, or possibly mediated by a ‘malnutrition‐inflammation complex syndrome’, which produces excessive oxidative stress and consequent inflammatory response . Aside from its role in protein‐energy storage as a malnutrition‐inflammation complex component, SA is also considered as a measure of inflammation and serves as an antioxidant . Our findings are in accordance with the findings of Liu et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…smoking), absorption disorder, hypercatabolic state, or possibly mediated by a ‘malnutrition‐inflammation complex syndrome’, which produces excessive oxidative stress and consequent inflammatory response . Aside from its role in protein‐energy storage as a malnutrition‐inflammation complex component, SA is also considered as a measure of inflammation and serves as an antioxidant . Our findings are in accordance with the findings of Liu et al .…”
Section: Discussionsupporting
confidence: 91%
“…Of note, the rate of HF re‐hospitalization in the present work was similar to a study performed in Canada (32.5% vs. 34.9%), suggesting similar health care quality . As a major component of PNI and CONUT, SA levels are also influenced by several pathophysiological conditions common in HF, such as haemodilution, transcapillary loss, enteric loss, hepatic dysfunction, and systemic inflammation . Given the fact that higher SA was associated with lower systemic white cell counts and CRP and that its robust relationship with various physical functions has been reported, the prognostic implication of lower SA further implicates pro‐inflammatory cascades as the hypothetical central pathophysiology in HFpEF from multiple co‐morbidities .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have previously shown that serum albumin, which is a component of the Child‐Pugh score, is lower in patients with cirrhosis with PVT compared to those without, but it is still unclear whether this finding is a mere epiphenomenon of the underlying liver disease, thereby unrelated to PVT development, or conversely has a pathophysiologic value in the context of clotting/platelet activation and eventually thrombosis . Because previous studies demonstrated an association between serum albumin and thrombosis in the setting of cardiovascular disease, the aim of the present study was to investigate if serum albumin was associated with PVT independently from Child‐Pugh score and if a biologic plausibility between serum albumin and thrombosis exists. As to the latter, we performed in vivo and in vitro studies to explore if albumin affects platelet activation and if so, what the underlying mechanism is, focusing in particular on its potential capability of modulating intracellular oxidative stress.…”
mentioning
confidence: 90%
“…[11][12][13] Furthermore, serum proteins such as albumin and prealbumin are used to de ne the nutritional status of adults and predict CVD risk. [14] • Non-traditional CVD risk factors include de ciencies of vitamins such as B 12 , B 6 , and folate, due to their association with hyperhomocysteinemia, a vascular risk factor that increases the risk of coronary heart disease. [15] In addition, an increase in the in ammatory marker C-reactive proteins is an indication of cognitive and physical impairments and is being reported as a crucial predictor of CVD risk and reduced survival amongst older adults.…”
Section: Introductionmentioning
confidence: 99%